Seeing Red : On Nonobjective Painting and Color Theory - Adler, Tracy L.; Agee, William C.; Cage, John; von Campenhausen, Christoph; Dickey, Tina; Evertz, Gabriele; Fehr, Michael; Gordon, James; Honnef, Klaus; Horowitz, Frederick A.; Roque, Georges; Swain, Robert; et al. (Köln : Salon Verlag & Edition Köln, 2004)
Albers, Josef ; Angeli, Marc ; Aubertin, Bernard ; Baumkötter, Stephan ; Bechinger, Thomas ; Becker, Engelbert ; Becker, Lutz ; Bhavsar, Natvar ; Bordarier, Stephane ; Carreiro, Joel ; Charalambou, Sotirakis ; Clarkson, David Frederic ; Conrad, Christiane ; Desgranges, Claudia ; Hazelet Drummond, Sally ; Dirnaichner, Helmut ; Evertz, Gabriele ; Gal, Andras ; Geiger, Rupprecht ; Gimblett, Max ; Girke, Raimund ; Gonschior, Kuno ; Günther, Monika ; Hafif, Marcia ; Hasselbach, Tinka von ; Hessling, Rosa M. ; Hofmann, Hans ; Hofschen, Edgar ; Honegger, Gottfried ; Humphrey, Ralph ; Joachim, Dorothee ; Jochims, Raimer ; Juchtmans, Jus ; Jusczcyk, James ; Kaiser, Raymund ; Kompa, Hartwig ; Lalic, Maria ; Longo, Vincent ; Marioni, Joseph ; Motherwell, Robert ; Neumann, A. Paola ; Noland, Kenneth ; Ohlson, Dough ; Parker, Ray ; Pattscheck, Sybille ; Pearson, Bruce ; Peck, George ; Piene, Otto ; Pihl, Thomas ; Pousette-Dart, Joanna ; Pousette-Dart, Richard ; Rögler, Michael ; Rose, Rolf ; Sagerman, Robert ; Sander, Karin ; Schade-Hasenberg, Gabriela ; Schomburg, Andrea ; Schreiber, Arne ; Schumacher, Emil ; Smith, Tony ; Stanczak, Julian ; Storm, Clinton ; Swain, Robert ; Thursz, Frederic Matys ; Tollens, Peter ; Villinger, Dieter ; Vombek, Rudolf ; de Vries, Herman ; Wells, Mac ; Winzer, Icke ; Wurmfeld, Sanford ; Youngerman, Jack
Seeing Red : On Nonobjective Painting and Color Theory, Hunter College/Bertha & Karl Leubsdorf Art Gallery New York, 2003-01-30. 2003-05-03, Seeing Red Part I (2003-01-30 t/m 2003-05-03) : Pioneers of Nonobjective Painting presented at The Bertha and Karl Leubsdorf Art Gallery, Seeing Red Part II : (2003-03-12 t/m 2003-04-26) Contemporary Nonobjective Painting presented at The Hunter College, Times Square Gallery Part III : Symposium (2003-03-14 & 2003-03-15) : Color as Experience : On Contemporary Nonobjective Painting and Color Theory, organized by the Hunter College Art Department in collaboration with the Goethe Institute New York.
boek